A new generation of high-ductile Dual-Phase steel reinforcing bars. (10th August 2018) - Caprili, Silvia; Salvatore, Walter; Valentini, Renzo; Ascanio, Cristiano; Luvarà, Gianbruno
Highlights: Steel rebars shall provide adequate ductility for construction in seismic areas. Durability problems affect TempCore® reinforcements causing decrease of ductility. Dual-Phase steels have good mechanical and durability performance. Industrial reinforcing steel plants need to be adapted to DP steel production. Production costs shall be limited allowing DP bars commercialization. Abstract: The development of a new typology of enhanced steel reinforcing bars is presented, including aspects related to the industrial production process, microstructural and mechanical characterization of achieved samples, is presented. Dual-Phase steels, provided by a ductile ferrite matrix in which a second hard martensite phase is embedded, are widely used in the automotive sector due to their excellent performance in terms of ductility and durability. For the same reasons, Dual-Phase steels can represent a valid alternative to current steel reinforcements – mainly TempCore® – that, as highlighted by the current scientific literature, are affected by relevant decrease of ductility in case of corrosion attack. The present paper shows the results of investigations executed to produce DP bars in reinforcing steel industrial plants; the experimental characterization is provided too.